Gaya Hidup Urban dan Konsumsi Simbolik: Fenomena Penggunaan Tumbler sebagai Simbol Status Sosial di Kalangan Mahasiswi Unsoed - Fatya Nurnayla; Joko Santoso; Amalia Nur Ramadhani (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2025)
This study aims to understand how the use of high-end brand tumblers by female students at Jenderal Soedirman University (Unsoed) represents urban lifestyle and functions as a symbol of social status and what are the reasons they choose to use tumblers. A qualitative approach was employed through in-depth interviews with purposively selected informants, including users of both high-end brand and non-brand tumblers. The findings reveal that tumbler usage has shifted beyond practical needs and has become part of symbolic consumption reflecting identity, taste, and social position. Students choose tumblers based on design, aesthetics, exclusivity, and social influences such as peers, family, social media, and the phenomenon of Fear of Missing Out (FoMO). Moreover, high-end brand tumblers are perceived as worth the price due to their quality and associated social image. Social media and influencers play a significant role in shaping perceptions and expanding tumbler usage trends. This study concludes that tumblers have transformed into symbols of modern lifestyle among students, marking a shift from functional consumption to symbolic consumption, as explained by Jean Baudrillard’s theory.